1990
DOI: 10.1037/0278-6133.9.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity, social interactions, and physical environment on physical activity in preschoolers.

Abstract: Examined demographic, environmental, and parent-child interactional correlates of physical activity in a group of 222 preschoolers. Activity levels were assessed with a system that quantified directly observed physical activity in the natural environment. Using regression-modeling procedures, results revealed a significant relationship between (a) child's relative weight, parental weight status, and percentage of time spent outdoors (environment) and (b) children's activity levels. Parental obesity was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
2
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 26 publications
5
120
2
7
Order By: Relevance
“…This speculation is supported by earlier studies indicating that time spent outdoors is associated with a higher amount of physical activity (Klesges et al 1990), and a positive relationship between high level of play activities and gross motor skills (Sääkslahti et al 1999). Earlier studies using different measures than ours have indicated weak and conflicting directions in the relationships between FMS and MVPA intensity in this age group (Cliff et al 2009;Fisher et al 2005;Williams et al 2008).…”
Section: Relationships Between Motor Skills and Activitysupporting
confidence: 69%
“…This speculation is supported by earlier studies indicating that time spent outdoors is associated with a higher amount of physical activity (Klesges et al 1990), and a positive relationship between high level of play activities and gross motor skills (Sääkslahti et al 1999). Earlier studies using different measures than ours have indicated weak and conflicting directions in the relationships between FMS and MVPA intensity in this age group (Cliff et al 2009;Fisher et al 2005;Williams et al 2008).…”
Section: Relationships Between Motor Skills and Activitysupporting
confidence: 69%
“…Consistently, Klesges et al (1990) reported a correlation coefficient of 0.34 between outdoor time and physical activity in pre-schoolers. Similar correlations have been found by Burdette et al (2004).…”
Section: Outdoor Time Physical Activity and Overweightmentioning
confidence: 53%
“…Sedentary lifestyle is one of the factors associated with the increased prevalence of obesity in modern society (Klesges et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Barnstable et al (1986) note that the single best predictor of weight loss in an adult behavior modi®cation program was the change in food consumption. Increased awareness of health-promoting nutrition and stimulus control techniques are intended to limit the individual's exposure to food and thus prevent incidental eating (Wadden, 1992).Sedentary lifestyle is one of the factors associated with the increased prevalence of obesity in modern society (Klesges et al, 1990).Leisure time is an important determinant in children's weight balance. A linear relationship exists between the hours of daily television viewing and childhood obesity owing to the more sedentary life-style encouraged by watching television and the greater exposure of the viewer to advertisements promoting food products (Dietz & Gortmaker 1985).…”
mentioning
confidence: 99%